2017
DOI: 10.1007/s00125-017-4400-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived racism and incident diabetes in the Black Women’s Health Study

Abstract: Aims To assess the association of perceived racism with type 2 diabetes, and the possible mediating influence of diet and body mass index (BMI). Methods The Black Women’s Health Study, a follow-up of 59,000 African-American women, begun in 1995. Over 16 years 5,344 incident cases of diabetes occurred during 576,577 person-years. Cox proportional hazards models were used to estimated hazard ratios (HRs) and 95% confidence intervals (CIs) for categories of “everyday” racism (interpersonal racism in daily life)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Other studies found that perceived discrimination impacted health behaviors (64) and that American Indian women with diabetes who reported perceived discrimination completed fewer diabetes services, which placed them at increased risk for comorbidities of diabetes (55); these findings support the notion that discrimination is associated with an increased risk of incident diabetes (147). Thus, chronic stress due to racism and discrimination can affect diabetes outcomes (12,71,144). However, there is a dearth of interventions that include strategies to address racism or discrimination as factors related to diabetes outcomes.…”
Section: Sociopolitical Contextmentioning
confidence: 59%
See 1 more Smart Citation
“…Other studies found that perceived discrimination impacted health behaviors (64) and that American Indian women with diabetes who reported perceived discrimination completed fewer diabetes services, which placed them at increased risk for comorbidities of diabetes (55); these findings support the notion that discrimination is associated with an increased risk of incident diabetes (147). Thus, chronic stress due to racism and discrimination can affect diabetes outcomes (12,71,144). However, there is a dearth of interventions that include strategies to address racism or discrimination as factors related to diabetes outcomes.…”
Section: Sociopolitical Contextmentioning
confidence: 59%
“…The For the Sake of All project described the impact of various policies (including financial and housing) and their link to discriminatory practices and negative health and diabetes outcomes of the black population in St. Louis (110). The Black Women's Health Study, a follow-up of 59,000 African American women, found that women who perceived a high level of everyday racism had a 31% increased risk of diabetes; those reporting exposures to the highest levels of lifetime racism had a 16% increased risk of T2DM (12). Other studies found that perceived discrimination impacted health behaviors (64) and that American Indian women with diabetes who reported perceived discrimination completed fewer diabetes services, which placed them at increased risk for comorbidities of diabetes (55); these findings support the notion that discrimination is associated with an increased risk of incident diabetes (147).…”
Section: Sociopolitical Contextmentioning
confidence: 99%
“…Some investigations have been conducted of the health effects of racism or discrimination. These findings suggest that racism or discrimination experienced by African Americans may lead to higher levels of social strain and contribute to higher inflammation and diabetes risk (Bacon et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…The Black Women's Health Study (BWHS), a follow‐up study of 59,000 black women, has queried participants on experiences of racism and subjective cognitive function (SCF). In prior analyses in the BWHS, greater experiences of racism were associated with increases in incidence of breast cancer, 20 asthma, 21 type 2 diabetes, 14 and obesity, 22 and with the prevalence of insomnia 13 . We hypothesized that greater experiences of racism would be associated with lower levels of SCF.…”
Section: Introductionmentioning
confidence: 93%
“…Experiences of racism are common among African Americans, with 50% or more respondents to a 2017 nationally representative survey reporting experiences of institutional racism (eg, having been discriminated against in pay or promotions in the workplace) and daily interpersonal racism (eg, having experienced racial slurs) 11 . These institutional and daily forms of racism have been associated with increased risks of various conditions that can impair cognition, including depression, 12 poor sleep, 13 type 2 diabetes, 14 and hypertension 15 . Two experimental studies have reported immediate adverse effects on cognition when African American subjects were exposed to fictional vignettes describing discrimination, 16 or when cognitive tests were administered by a white person and levels of perceived discrimination were high 17 .…”
Section: Introductionmentioning
confidence: 99%